Analisis Faktor Risiko Kejadian Keracunan Pestisida Anorganik Pada Enzim Cholinesterase Dalam Darah Petani - MG Catur Yuantari; Cinta Nur Trya (Dian Nuswantoro Semarang, 2020)
Background and objectives: improved agricultural farmers using pesticides. The pesticide was toxic materials so it was harmful to health and the environment. The purpose of this research was to know the factors associated with the occurrence of inorganic pesticides poisoning against the enzyme cholinesterase in the blood on the farmers.Methodology: this research used analytic observational research-using the crossed sectional studied design. The sample in this research was the 45 respondents. A researched instrument in the form of a structured questionnaire, the taking of a blood sample to test cholinesterase, with the ethics commission with a number of 128/EC/FKM/2017. Results the statistical results could be concluded that there was no relationship between age (p 0. 18), educational leveled (p 0,546), age (p 0. 279), the number of pesticides (p 0. 58), how management (p 1. 000), the completeness of ppe (personal protective equipment) (p 1. 000) on the incidence of pesticides poisoning in inorganic horticultural farmers in the village of Batur, Getasan, Semarang regency. However, the relationship between dose (p 0. 006) and the incidence of pesticide poisoning in organic horticulture farmers in the village of Batur, Getasan, Semarang regency.Conclusions: the farmers should pay more attention to the completeness of the personal time off work, suggested the existence of health services for the management and construction of health workers and for other researchers expected the presence of further researched towards the factors associated with the incidence of pesticide poisoning with larger populations as well as the wider scopeKeywords: Cholinesterase, Horticulture Farmers, Pesticide Poisoning